Development of Streaming Media Security using Geolocation - Agus Sulaiman; Marza Ihsan Marzuki (Asosiasi Staf Akademik Perguruan Tinggi Seluruh Indonesia (ASASI), 2022)
Video streaming is digital data that is shared over the internet network. Streaming video through security protection techniques creates a security that is expected to protect intellectual property rights because there is data transfer through the internet. The use of password-based and token-based authentication is a security technology widely used in exchanging data and information between the client and server. However, this method is currently not sufficient to represent a security system using a Geographic Information System. Geolocation is a system or designation of geographic location in a world on an object that is connected via the internet network. IP geolocation can be used to define a particular IP address based on the geographic location from which the device is connected to the internet. The benefit of applying this technology is that each individual or organization can identify the location of a device connected to the internet. The study will use applied research and quantitative data with the implementation of a Geographic Information System that includes the creation of a security architecture on video streaming using Geolocation and test variables that can be used as a basis for analysis to describe the results of the testers. The test results with a random access server system from 50 countries with a blacklist and whitelist grouping mapping system show a success rate of 80%. Based on the results obtained from the use of live streaming security with Geolocation, it can be implemented to improve the security system.